Leisure, Rekreasi, Pariwisata dalam Berbagai Dimensi Metropolitan - Myra P. Gunawan (Journal of Regional and City Planning, 2007)
Leisure, recreation and tourism have been part of urban and metropolitan life. Citizen of metropolitan with various lifestyles need some spaces, along with supporting facilities for leisure and recreation which are shared with tourists and other visitors. Planning for providing spaces and supporting facilities for leisure, recreation and tourism is surely an integral part of urban planning. This article explains the urban dimension of leisure, recreation and tourism. Those three terms are deï¬ned from various perspectives. Analysis on why people moving or going to urban areas and their implication on leisure, recreation and tourism activities are elaborated. Indonesian illustration on those terms in the context of urban planning are discussed. Finally a discussion on spatial and planning implication of leisure, recreation and tourism are given.Keywords: leisure, recreation, tourism, spatial planning